2013
DOI: 10.3899/jrheum.130270
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical, Pathological, and Genetic Characterization of Methotrexate-associated Lymphoproliferative Disorders

Abstract: Our data demonstrate that patients in the EBVMCU, a specific clinical subgroup of MTX-LPD, had a better clinical outcome when MTX was withdrawn than did other patients with MTX-LPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 24 publications
4
81
2
Order By: Relevance
“…The pathognomonic histology of EBVMCU comprises of ulcers and polymorphous mixed lymphocytic infiltrates including atypical large B-cells and Reed-Sternberg-like cells uniformly expressing CD30 with EBER positivity, thus EBVMCU is considered as a clinical subtype of EBVassociated LPD (8). A recent study analyzing MTXassociated LPD (MTX-LPD) occurring in 20 patients with RA and 1 patient with polymyositis demonstrated that EB-VMCU was found in 24% of MTX-LPD and in 42% of EBV-positive MTX-LPD, indicating that EBVMCU constitutes a certain fraction of MTX-LPD (9). However, in the present case, atypical large B cells or CD30-positive ReedSternberg-like cells and other types of immunoblastic cells were not found in ulcerative lesion, suggesting a pathogenesis distinct from that of EBVMCU underlies the perforated ulcer formation in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…The pathognomonic histology of EBVMCU comprises of ulcers and polymorphous mixed lymphocytic infiltrates including atypical large B-cells and Reed-Sternberg-like cells uniformly expressing CD30 with EBER positivity, thus EBVMCU is considered as a clinical subtype of EBVassociated LPD (8). A recent study analyzing MTXassociated LPD (MTX-LPD) occurring in 20 patients with RA and 1 patient with polymyositis demonstrated that EB-VMCU was found in 24% of MTX-LPD and in 42% of EBV-positive MTX-LPD, indicating that EBVMCU constitutes a certain fraction of MTX-LPD (9). However, in the present case, atypical large B cells or CD30-positive ReedSternberg-like cells and other types of immunoblastic cells were not found in ulcerative lesion, suggesting a pathogenesis distinct from that of EBVMCU underlies the perforated ulcer formation in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization in 2008 defined a broad category of “posttransplantation and iatrogenic” LPDs that recognizes iatrogenic immunosuppression as a pathogenic factor, with MTX included as an etiologic agent of iatrogenic immunodeficiency-associated LPDs 2, 3, 4. The proposed mechanism by which this occurs is via MTX-induced suppression of EBV-specific cytotoxic T cells, which promotes the reactivation of EBV-specific B cells that proliferate 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism by which this occurs is via MTX-induced suppression of EBV-specific cytotoxic T cells, which promotes the reactivation of EBV-specific B cells that proliferate 4 . Although MTX-induced LPDs in RA patients have been discussed in previous case reports, lesions presenting on the skin and oral cavity were rarely reported in the literature 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…15 If Despite the advent of new effective biologic agents, MTX is still recommended as the most effective drug and as an anchor drug to enhance or maintain the efficacy of biologic agents. We should keep in mind the association between MTX and occurrences of oral LPDs.…”
Section: 4-8mentioning
confidence: 99%